Kalimantan Narratives of The Wounded Earth: Mirrors of Sumatra Disaster - Novita Dewi (UIN Raden Mas Said Surakarta, 2026)
This article aims to see how environmental degradation in Kalimantan, depicted in two Indonesian short stories, “Pohon Pongo” by Rinto Andriono and “Pekik Burung Kedasi di Tepi Kahayan” by Han Gagas, parallels the current Sumatra flash floods. A comparative analysis in light of Econarrative is applied to explore the interplay of Narrative, Science, and Action in both stories, filling gaps in Environmental Humanities research that generally rely on ecocritical theories. The article shows that the characters’ efforts to save orangutans and confront brutal mining activities are critiques of corrupt, incapable leadership and of industrial greed that exacerbate ecological damage. Through salient storytelling that combines literary perspectives, scientific outlooks, and a call for restoration, the short stories are mirrors of disasters, serving as profound cautionary tales for conservation and environmental advocacy. The beneficial narrativization of conflicts surrounding ethics and moral dilemmas makes both stories relatable to human experiences in dealing with real-world ecological realities. Econarrative reading reveals the short stories’ emphasis on the value of local knowledge and the spiritual connection between humans and nature. As such, integrating local-based literary works in sustainable education is highly recommended to foster awareness of today’s global ecological problems.